Effect of a 24-week supervised concurrent exercise intervention on fecal microbiota diversity and composition in young sedentary adults: the ACTIBATE randomized controlled trial - Martinez-Tellez, Borja; Xu, Huiwen; Ortiz-Alvarez, Lourdes; Rodríguez- García, Carmen; Schönke, Milena; Jurado-Fasoli, Lucas; Osuna-Prieto, Francisco J.; Alcantara, Juan M.A.; Acosta, Francisco M.; Amaro-Gahete, Francisco J.; Folkerts, Gert; Vilchez-Vargas, Ramiro; et al. (Clinical Nutrition, 2025)
Background. Numerous physiological responses to exercise are observed in humans, yet the effects of long-term exercise and varying intensities on the diversity and composition of human fecal microbiota remain unclear. We investigated the effect of a 24-week supervised concurrent exercise intervention, at moderate and vigorous intensities, on fecal microbiota diversity and composition in young adults. Methods. This ancillary study was based on data from the ACTIBATE randomized controlled trial (ClinicalTrials.gov ID: NCT02365129), and included adults (aged 18-25 years, 70% female) that were randomized to (i) a control group (CON: no exercise, n=20), (ii) a moderate-intensity exercise group (MOD-EX, n=21), and (iii) a vigorous-intensity exercise group (VIG-EX, n=20). Fecal samples were collected before and after the 24-week exercise intervention, and the diversity and composition of the fecal microbiota were analyzed by 16S rRNA sequencing. Inferential functional profiling of the fecal microbiota was performed and correlations between microbial changes and cardiometabolic outcomes were assessed. Results. Exercise did not modify beta or alpha diversities regardless of the intensity (all P≥0.062). The relative abundance of the Erysipelotrichaceae family (Bacillota phylum) (-0.3±1.2%; P=0.031) was however reduced in the VIG-EX group. Coprococcus was the only genus showed a significant difference between MOD-EX and VIG-EX after the intervention, with its relative abundance increasing in MOD-EX (+0.4±0.6%; P=0.005). None of these changes were related to the exercise-induced cardiometabolic benefits (all P≥0.05). Conclusions. In young adults, a 24-week supervised concurrent exercise program, at moderate and vigorous intensities, resulted in minor changes in fecal microbiota composition, while neither alpha nor beta diversities were affected.
Keywords: endurance exercise, gut, microbiome, resistance exercise, succinate.; endurance exercise; gut; microbiome; resistance exercise; succinate; Scopus